The Role of the Village Consultative Body in Village Governance in Mongolat Village, Telaga District, Gorontalo Regency - Harsono Ahmad (Universitas Bina Mandiri Gorontalo, 2025)
This study aims to determine and obtain data regarding the implementation of the main tasks and functions of the Village Consultative Body in the administration of government, and obtain data on the factors that influence the implementation of the main tasks and functions of the Village Consultative Body in the administration of government in Mongolato Village, Telaga District, Gorontalo Regency. The research method uses data collection techniques through, observation, interviews, and documentation. The data obtained from the research results are processed using qualitative analysis to find out and obtain data regarding the implementation of the main tasks and functions of the Village Consultative Body in the administration of government and obtain data on what factors influence the implementation of the main tasks and functions of the Village Consultative Body in the administration of government. The results of this study indicate that the implementation of the main tasks of the BPD in the administration of government has not been fully carried out optimally because only three main tasks are carried out namely accommodating and channelling the aspirations of the community, forming a village head election committee and the process of discussion and stipulation of village regulations together with the village head, out of six the main tasks that have been determined by the Government Regulation on Villages. the factors that influence the implementation of the main tasks and supervisory functions are influenced by two factors, namely the driving factor which includes community support or participation, and a good cooperative relationship between the Village Consultative Body and the Village Government. Whereas the second factor is the inhibiting factor which includes the lack of benefits provided to the members involved, facilities and infrastructure, lack of Human Resources to fill membership and the existence of a society that is either pro or contra to each decision made.